SILENCE VOICES AND CULTURIZED MYTHS: ORIENTALIST READINGS OF JOSEPH CONRAD'S LORD JIM: Suara-suara yang Dibungkam dan Mitos yang Membudaya: Pembacaan Orientalis terhadap Lord Jim karya Joseph Conrad - Wajiran, Wajiran; Sumarlan, Iman; Anisa Sari, Eka (BASIS (Bahasa dan Sastra Inggris), 2025)
This study aims to critically examine Joseph Conrad’s Lord Jim through the lens of Edward Said’s theory of Orientalism, focusing on how the novel represents the East as subordinate to Western ideological and moral authority. Employing a qualitative literary analysis, this research explores narrative structure, characterization, and setting to reveal how the novel systematically marginalizes Eastern voices and constructs the East as a passive backdrop for the psychological and moral journey of the Western protagonist, Jim. Key findings show that the Indigenous characters in Patusan are denied subjectivity and interiority, their perspectives filtered entirely through the Western narrator, Marlow. The narrative elevates Jim to a position of moral superiority and leadership, reinforcing colonial myths of the “white savior” and the supposed dependency of Eastern societies on Western governance. The absence of Eastern perspectives in the novel underscores the epistemological dominance of the West, making Lord Jim not a true intercultural dialogue, but a monologue that serves Western self-definition. The study concludes that Conrad’s novel, despite its literary complexity, perpetuates Orientalist discourse by silencing the East and reinforcing hierarchical binaries between the West and the non-West. Future research is encouraged to compare such colonial narratives with postcolonial works that reclaim indigenous voices.